The Differences of early detection Upper Respiratory Infection (ISPA) by using MTBS Standard and MTBS Flashcard at Kota Semarang Public Health - Nina Indriyawati; Lucia Endang Hartati YK; Titin Suheri (Jurnal Riset Kesehatan, 2013)
The aim of this study is to analize differences of early detection upper respiratory infection by using MTBS standard and MTBS flashcard at kota Semarang Public Health. Research design used comparison study with cross sectional design. 16 nurses/midwiferies ware taken for sample. Instruments used MTBS standard and MTBS flashcard. Quesionair was used for identify the level of knowledge about upper respiratory infection and MTBS that have already validited by expert.The result of the study shows that the level of knowledge about upper respiratory infection and MTBS are at category good (100% and 94%, respectively). Based on the content, there were no different eatherMTBS flashcard or MTBS standard (88%). There were found differences in the attractive designs, 14 respondents (88%) were more interest in MTBS flashcard than MTBS standard. MTBS flashcard (94%) was more efective for early detection upper respiratory infection than MTBS standarad (44%). The time was used for detect upper respiratory infection was different. The mean of time used for MTBS flashcard was 4 minutes (SD=1.2) and MTBS standard was 7 minutes (SD=3.1).